STRATEGI BRANDING SANGGAR SENI SEKAR PANDAN MELALUI MEDIA SOSIAL - Pradhana, Yudha; Prakosa, Adi; Kadarsih, Dinar; Wiandari, Divani; Zahrani, Ranisha Eka; Rizkiansyah, Fadhly Akbar (LPPM-PMP Universitas Tidar, 2023)
Sekar Pandan Art Studio is a studio that still maintains the authenticity of Cirebon Mask Dance. Cirebon Mask Dance is an ancestral heritage which is one of the characteristics of Cirebon City. Therefore, an effective and efficient strategy is needed so that this goal can be achieved. This research will examine and analyze the strategy of the Sekar Pandan Art Studio in an effort to carry out branding on social media. The aim of this research is to understand and provide ideas regarding the importance of implementing a branding strategy for a community or organization that has been established for a long time in order to maintain its existence by using social media. Data was taken from observation transcripts as well as conducting direct interviews with the management and person in charge of the Sekar Pandan Art Studio. The research approach used by researchers is a descriptive qualitative approach which aims to analyze the strategies used by the studio in an effort to carry out branding on social media.